China’s Intervention Policy in Myanmar Facing Challenges from India - Lê Hoàng, Kiệt (MultiTech Publisher, 2023)
In the context of the 21st century, Myanmar holds a significant geopolitical position, serving as a hotbed of competition between India and China in the Indian Ocean and Southeast Asia region. To counter India’s influence, China has employed various tools to increase its sway in Myanmar. This article investigates China’s intervention policies in Myanmar in the face of challenges from India. The research results indicate that China is implementing four main policies to intervene in Myanmar: (1) Approaching political factions; (2) Exploiting ethnic issues, particularly the Rohingya; (3) Creating economic dependence through investment and trade; (4) Enhancing military and defense cooperation. However, Myanmar’s policies have undergone numerous changes, causing China’s influence to waver. Nevertheless, in the current volatile context, Myanmar tends to rely on China economically and militarily. This has posed challenges to India’s position, especially since the National League for Democracy (NLD) leader - Aung San Suu Kyi was ousted.